LEGAL REGULATION OF THE ENVIRONMENTAL FUNCTION OF THE STATE IN CONTEXT OF HUMAN RIGHTS AND CITIZENS - Logvynenko, Olena I.; Khomyachenko, Svitlana I. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The authors of the article made an attempt to investigate the place and role of the state’s ecological function in Ukraine, an analysis of the norms of the current legislation of Ukraine on the basis of which the legal regulation of the state’s ecological function is carried out. Specific features of environmental rights are disclosed, and issues of compliance with environmental legislation in the sphere of use and protection of forest resources are considered separately.